2020
DOI: 10.21638/spbu03.2020.305
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of vigilance in geese: influence of flock size and distance to the source of disturbance

Abstract: Left-eye preference, implicating right hemisphere advantage, is typical for vigilant behaviour of many vertebrates. Nevertheless, lateralization of vigilance may be manifested in other ways, such as different reactions to the danger viewed with the right and left eye. Here, we studied one-side biases in the orientation of white-fronted geese Anser albifrons feeding in flocks at different distances to the source of anthropogenic disturbance (a road with traffic) and in flocks of different sizes. The birds which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Birds had a signi cant bias in the observation of the source of disturbance and hadn't in the observation of the leading partner. This result corresponds to the previous funding for White-fronted geese and Barnacle geese (Zaynagutdinova et al 2020). In this study, geese had the visual lateralisation bias in following the partner throughout the entire annual cycle, but they hadn't any preferences under the disturbing conditions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Birds had a signi cant bias in the observation of the source of disturbance and hadn't in the observation of the leading partner. This result corresponds to the previous funding for White-fronted geese and Barnacle geese (Zaynagutdinova et al 2020). In this study, geese had the visual lateralisation bias in following the partner throughout the entire annual cycle, but they hadn't any preferences under the disturbing conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, it was found that disturbances could in uence the manifestation of the visual lateralisation bias, at least during the interaction between partners in the wild. For example, visual lateralisation was manifested in routine behaviours of Barnacle geese (Branta leucopsis) and Greater white-fronted geese (Anser albifrons), but lateralisation was lacking in disturbing conditions (Zaynagutdinova et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that the left eye (right hemisphere) use provides an advantage in the assessment of potential threat (Blumstein et al, 2018). Similarly, white-fronted geese seem to show improved recognition of potential threats when monitoring them with the left eye (Zaynagutdinova et al, 2020). Our results do not suggest that the use of the left or right eye affects the speed of assessment of a potential threat in steppe marmots.…”
Section: Lateralization In Relation To Approach and Flight Initiation...mentioning
confidence: 55%
“…The right hemisphere advantage was found, for example, in antipredator responses (e.g., Lippolis et al 2005 ) and the perception of fearful social cues ( Siniscalchi et al 2018 ). Among birds, the geese which were closer to the source of anthropogenic disturbance (a trafficked road) were found to be more prone to use the left eye ( Zaynagutdinova et al 2020 ). Thus, the right hemisphere is responsible for the control of both emergency and social responses probably because of the involvement of the same cognitive abilities e.g., continuous attention and high reactivity.…”
Section: Discussionmentioning
confidence: 99%